INT Issue 10: Expat Places/Spaces/Baggage CFP - Furijan, Helene; Gatley, Julia (Interstices: Journal of Architecture and Related Arts, 1970)
Interstices 9 Call for PapersExpatPlaces, Spaces, Baggage.Our present is marked by intense human displacement. For some, nomadism is a choice made possible by global hyper-connection; while others are forced into nomadism. Expatriates take up residence away from home. This residence is always viewed as temporary, even though it may become permanent. Multiple residencies may suspend people between homes. Architectural practice is not alone in having been transformed by the hybridities of expertise and location brought about by expanded networks.A new geography is established by the multitude as the productive flow of bodies define new rivers and ports. The cities of the earth will become... temporary residences and networks of the mass distribution of living humanity.[ Negri and Hardt, Empire, (Cambridge, Mass: Harvard University Press, 2000), p397 ]In Deleuze and Guattari’s nomadology the nomad inhabits a milieu rather than a place; which is to say the nomad lives relationally rather than territorially, interested primarily in the mobilisation of paths. Similar displacements are observable in other theories of mobility and the outside:  Bhabha’s postcolonial unhomeliness; Augé’s non-places of supermodernity; Kristeva’s experience of foreignness. Expatriation might also serve as a diagram for all journeys away from the interior to take up residence in the exterior.What are the spaces and structures of the expatriate? What are the consequences for architecture and urbanism of a world defined by flows, circulation and temporary alliances? Is this a purely contemporary condition, or one with historical precedents? What is it to refuse home? How does an experience of the outside inform architectural works?Issue 9 of Interstices invites contributions examining the spatiality of expats and their baggage. Interstices 9: Expat. Submission InstructionsRefereed papers must not exceed 5000 words (including endnotes; excluding bibliography), non-refereed full papers 2500 words, and reviews 1000 words (longer papers are only accepted in special circumstances and with prior negotiation). Text must be formatted in accordance with the APA’s Publication Manual (5th edition; notes for contributors will be sent out to authors whose contributions have been accepted). Spelling should follow UK English and quotations must be translated into English. All papers must be submitted electronically in MS Word or RTF format, initially with .jpg image files of 300dpi (approx. 10% larger than the intended size of reproduction). Figures should be numbered clearly in the text, and image captions and credits must be included with submissions. It is the responsibility of the author to secure permissions for image use and pay any reproduction fees. A brief author bio of approx. 150 worlds must also be included.Deadline for submissions: 5 December 2007.Submit to: The Editors, Interstices 09Helene Furjan furjan@design.upenn.eduJulia Gatley julia.gatley@auckland.ac.nzFor Notes for Contributors, please visit our website http://www.interstices.auckland.ac.nz and download from the page Publications.Interstices: A Journal of Architecture and Related Arts is an open forum for the dissemination of thought and practices in architecture and related arts. It is a non-profit journal published jointly once a year by the School of Architecture and Planning, The University of Auckland, and the School of Art and Design, AUT University.Dr Helene FurjanDepartment of ArchitectureSchool of DesignThe University of Pennsylvania207 Meyerson HallPhiladelphiaPA 19104-6311USA P. +1 215 898 5728F. +1 215 573 2192E. furjan@design.upenn.edu Dr Julia GatleySchool of Architecture and PlanningThe University of AucklandPrivate Bag 92019Auckland 1142New Zealand P. +64 9 373 7599 ext 84656F. +64 9 373 7694E. julia.gatley@auckland.ac.nz